Citizen budget project with crowdsourcing concept – identification of attitudes - Niedzielski, Piotr Jacek; Henhappel, Sylwia; Zioło, Magdalena; Klimek, Jordan; Klimek, Julia Anna; Grześ, Anna (Journal of Modern Science, 2025)
Objectives This paper aims to identify community attitudes towards implemented local budgets and to make a comparative assessment of these community attitudes in different locations. Material and methods The study was carried out based on an analysis of the foundational data, particularly the reports of the civic budgets. The entire available period of implementation of civic budgets, i.e. 2014-2024 in Bialystok and Szczecin, was analyzed. Results Data on the implementation of civic budgets in the two cities show two different trends in the attitudes of local communities. Despite similar legal and social conditions and the same maturity period, the Bialystok community is increasing its involvement in the civic budget idea, while the Szczecin community is reducing it. Conclusions Our analyses indicate that the use of crowd knowledge in these two areas, i.e. idea generation and idea evaluation, is used to a different extent in the implementation of the civic budget idea. We suppose that the differences in the attitudes of the indicated local communities are mainly socio-cultural and political in nature. We point to the necessary measures to reduce the decline in activity and thus the increase in local community dissatisfaction.